Aflatoxins contamination in processed cassava in Malawi and Zambia - Chiona, M.; Ntawuruhunga, Pheneas; Benesi, I.R.M.; Matumba, L.; Moyo, C. (2014)
Strains of the Aspergillusfungi, especially A.flavus and A. parasiticus,primarily produce aflatoxins which are a major health concern to man and livestock because of their acute and chronic health effects. Aflatoxins pose the greatest risk to health in tropical Africa because of their widespread prevalence and high toxicity; carcinogenic (cause liver and esophageal cancer)effect, immune system suppressing and anti-nutritional contaminants in many food commodities and even cause death. Aflatoxins havealsobeen reported to compromise vaccine efficacy in experimental animals. Due to the seriousness of aflatoxins, international agencies have restricted levels of aflatoxins to 20 ppb in food materials as the maximum permissible level in the United States and 4 ppb total aflatoxins and under 2 ppb aflatoxin B1 in Europe. These regulations directed at minimizing human exposure to aflatoxins results in severe economic loss to producers, processors and marketers of the contaminated crop.A study was conducted in Malawi and Zambiato assess the level of fungal and mycotoxins’contamination in commonly processed cassava products. A total of 92 and 88 samples of processed cassava productscomprisingmakaka, flour, kanyakaska, kadonoska, scrapes and grates were collected in the rainy season of 2008 and 2009in Malawi, respectively. Further,22 samples of processed cassava products comprising dried cassava chips and flour were collected in the rainyseason of 2009 in Zambia. The sampleswere analyzed for fungal and aflatoxins B1, B2, G1 and G2 contamination using the Romer mini-column method andthe VICAM AflaTest immunoaffinity fluorometric method.None of the samples in 2008 werecontaminated with aflatoxins. Similar results were obtained in 2009 with almost all the samplesin Malawi and Zambia having aflatoxinlevels much lower (<2.0?g/kg in Malawi and <4.2 ?g/kgin Zambia) than the Codex Alimentarius Commission (CAC) maximum permissible level of aflatoxins of 10.0 ?g/kg,implying that the cassava products analyzed were safe for human consumption. However, further studies are needed to covera larger sample size over a period of a year to represent all seasons in the cassavaproducing andconsuming areasandconclusively make certain the safety of these products for human consumption.